2018
DOI: 10.1002/cpt.1223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SLCO1B1 Pharmacogenetic Testing on Patient and Healthcare Outcomes: A Systematic Review

Abstract: Demonstrated improvements in patient outcomes will facilitate the clinical implementation of pharmacogenetic testing. Using the association between solute carrier organic anion transporter family member 1B1 (SLCO1B1) and statin-associated muscle symptoms (SAMSs) as a model, we conducted a systematic review of patient outcomes after delivery of SLCO1B1 results. Using PubMed and Embase searches through December 19, 2017, we identified 37 eligible records reporting preliminary or final outcomes, including six stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 80 publications
(263 reference statements)
0
11
0
Order By: Relevance
“…CPIC has published a clinical guideline on the management of patients who have specific SLCO1B1 genetic variants, specifically with respect to statin prescription and dosing. A recent systematic review reported that genotype testing may influence the prescribing of statins among high-risk patients, but the impact of SIM or cardiovascular events was not reported (Vassy et al, 2019). Peyser et al (2018) conducted a prospective randomized SLCO1B1 genotype-guided statin therapy trial in 159 patients who stopped taking statins because of a history of statin myalgia.…”
Section: Discussionmentioning
confidence: 99%
“…CPIC has published a clinical guideline on the management of patients who have specific SLCO1B1 genetic variants, specifically with respect to statin prescription and dosing. A recent systematic review reported that genotype testing may influence the prescribing of statins among high-risk patients, but the impact of SIM or cardiovascular events was not reported (Vassy et al, 2019). Peyser et al (2018) conducted a prospective randomized SLCO1B1 genotype-guided statin therapy trial in 159 patients who stopped taking statins because of a history of statin myalgia.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports, however, report patient outcomes after the delivery of these pharmacogenetic results, with the most notable finding being a pilot trial that observed short-term improvements in LDL after SLCO1B1 testing (10 mg/dl decrease in LDL) [14]. However, there is some evidence that suggests the implication of SLCO1B1 results can change the prescribing pattern for providers (15). Based on the SLCO1B1 testing results and genotype determination, therapy is initiated as following: This personalized testing method allows patients to uncover their genetic make-up and the factors influencing it.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of four RCTs and 12 non-randomised studies of patients taking high dose simvastatin therapy of 80 mg/day for the 85 participants with myopathy their odds ratio for myopathy was 4.5 (95% CI 2.6-7.7) per copy of the C allele, and 16.9 (95% CI 4.7-61.1) for those with two alleles (CC) compared to the normal TT homozygotes [110]. The PharmGKB database assesses the evidence as level A (highest level evidence) that statins cause myopathy in patients with gene SLCO1B1 allele variants [111].…”
Section: Statins and Myopathymentioning
confidence: 99%